Implementation of the Guided Inquiry Model Based on Big Book Media to Improve the Mathematics Learning Process and Outcomes in Grade IV of SDN 05/II Air Gemuruh - Putri Wulan Maya; Zulqoidi R. Habibie; Dhini Mufti (Master of Action Research in Mathematics Classroom, 2026)
This classroom action research wasconducted on 26 fourth-grade students at SDN 05/II Air Gemuruh. Based on initial observations, it was found that the learning process and outcomes of the participantswere still lacking. This was due to the fact that the learning process did not fullyfollow the principles of the independent curriculum, and the average test scores were still below the school's minimum passing grade of 75. This study applied the PTK method, which consisted of twocycles, each covering the stages of planning, implementation, observation, and reflection. The findings of the study showed that the application of the guided inquiry model based on big book media in data compilation material was very successful. Teacher performance increased from 90.95% in cycle I to 100% in cycle II. Student participation also increased from 71.16% to 95.08%, exceeding the success target of 75%. In terms of learning outcomes, student mastery increased from 69.23% (average score of 75) in cycle I to 92.30% (average score of 84.62) in cycle II. Overall, there was anincrease of 23.07% from the beginning to the end, which shows that the guided inquiry model based on big books was successful in improving student learning outcomes on the topic of fractions